2021
DOI: 10.3390/ijms221910343
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Exosomal miR-221 from Maternal Obesity Inhibits Angiogenesis via Targeting Angptl2

Abstract: Maternal obesity disrupts both placental angiogenesis and fetus development. However, the links between adipocytes and endothelial cells in maternal obesity are not fully understood. The aim of this study was to characterize exosome-enriched miRNA from obese sow’s adipose tissue and evaluate the effect on angiogenesis of endothelial cells. Plasma exosomes were isolated and analyzed by nanoparticle tracking analysis (NTA), electron morphological analysis, and protein marker expression. The number of exosomes wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…It was found that 12-month-old offspring of obese dams had increased body weight and fat mass and exhibited an elevated level of hepatic miR-582-3p and miR-582-5p [93]. Zhou et al characterised the exosomes from the adipose tissue of an obese sow and found they regulate endothelial cell migration and angiogenesis through miR-221 implicated in placental dysplasia during gestation [94]. A study analysed peroxisome proliferator-activated receptor (PPAR)-γ expression in cells of offspring from obese and overweight mothers and uncovered its relation with miRNAs [95].…”
Section: Mirnas Modulated During Maternal Obesitymentioning
confidence: 99%
“…It was found that 12-month-old offspring of obese dams had increased body weight and fat mass and exhibited an elevated level of hepatic miR-582-3p and miR-582-5p [93]. Zhou et al characterised the exosomes from the adipose tissue of an obese sow and found they regulate endothelial cell migration and angiogenesis through miR-221 implicated in placental dysplasia during gestation [94]. A study analysed peroxisome proliferator-activated receptor (PPAR)-γ expression in cells of offspring from obese and overweight mothers and uncovered its relation with miRNAs [95].…”
Section: Mirnas Modulated During Maternal Obesitymentioning
confidence: 99%
“…EVs derived from the human placenta could participate in regulating the maternal immune system and vascular network for successful pregnancy outcome 10–12 . The role of exosomes in placental vascular complications and pregnancy disorders also has been reported 13–16 . Our previous research indicated that exosomal miRNAs are important for regulating angiogenesis to maintain a normal pregnancy 17 .…”
Section: Introductionmentioning
confidence: 96%
“…[10][11][12] The role of exosomes in placental vascular complications and pregnancy disorders also has been reported. [13][14][15][16] Our previous research indicated that exosomal miRNAs are important for regulating angiogenesis to maintain a normal pregnancy. 17 We also found exosomes derived from women with preeclampsia could induce vascular dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Microvesicles carry various biological molecules, such as microRNAs (miRNAs), proteins and DNAs, which regulate the biological function of target cells 16 . Studies have reported that circulating vesicles inhibit endothelial cell angiogenesis through miR221‐mediated repression of Angpl2 17 . Eukaryotic translation initiation factor 4E binding protein 1 (4EBP1) is a translation inhibition protein family member.…”
Section: Introductionmentioning
confidence: 99%
“…16 Studies have reported that circulating vesicles inhibit endothelial cell angiogenesis through miR221-mediated repression of Angpl2. 17 Eukaryotic translation initiation factor 4E binding protein 1 (4EBP1) is a translation inhibition protein family member. However, 4EBP1 could also promote the translation process of VEGF, 18,19 HIF1α and BCL-2 20 under hypoxia conditions.…”
mentioning
confidence: 99%